Association of Proprotein Convertase Kexin/Type 9 with Atherosclerosis in People with Type 2 Diabetes Mellitus: a Systematic Review - Luthfia, Farissa; Wisnu, Wismandari; Tahapary, Dicky Levenus; Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Type 2 diabetes melitus is the leading cause of cardiovascular event with high level of low-density lipoprotein as the main predictor marker of atherosclerosis. PCSK9 plays a role in LDL-receptor regulation, its association with atherosclerosis had been investigated but the result is inconsistent. This study aimed to examine the association between PCSK9 level and atherosclerosis in people with type 2 diabetes. Methods. A systematic review was done in July 18 – September 02, 2020 and registered in PROSPERO. Risk of bias of each study was analyzed with Newcastle Ottawa scale tools. Studies involved in this systematic review then narratively analyzed by two independent reviewers. Results. There are 430 subjects involved from 4 studies. Guo, et al. reported that there was a significant association between PCSK9 level with atherosclerosis in type 2 diabetes melitus (OR: 1.12 (CI 95% 1.041 – 1.204), p: 0.002), those association was also reported by Ma, et al. with p value Conclusions. There is still insufficient evidence that show the association between PCSK9 level and atherosclerosis in type 2 DM. Therefore, longitudinal primary research is needed.